Purification, crystallization and structure determination of Thermotoga maritima CorA Magnesium transporter. - Nurhuda Nordin. (2010)
Magnesium is the most abundant divalent cation in cells. Despite its importance, the transport mechanism of magnesium remained poorly defined. Currently, CorA is used as the model to study magnesium transport across the cell. Three crystal structures of Thermotoga maritima CorA with the resolution of 2.9 – 3.9 angstroms have been available since 2006. These structures revealed a closed conformation induced by bound metal ions. Here we have successfully crystallized TMCorA in the absence of divalent cations by keeping the sample fractionated after gel filtration. Arguably, crystals grown in such conditions would result in an open conformation structure. By comparing the present structures and this new structure, we could deduce the transport mechanism of magnesium. Through the same method, we have also successfully crystallized TMCorA in the presence of only 1 mM Mg2+. Structures from these crystals may verify the function of the metal binding sites. We have also experimented purifying TMCorA by heating and centrifugation only. This form of purification has produced a relatively pure sample and formed crystals in the presence of lipids. The presence of these lipids may stabilize the structure and give rise to a better resolution. Taken together, we are one step closer to obtaining the open conformation structure and perhaps also a better resolution structure of TMCorA.